Editorial - Grilli, Matteo (Southern Journal for Contemporary History, 2022)
Oral sources play a fundamental role in the study of African history. Their use by historians in the form of “oral traditions” has been first defined theoretically and methodologically by Jan Vansina, who is still the main reference in this field. While Vansina himself had stated clearly that his approach was not “limited to any particular period or place” , oral traditions have been primarily deployed to investigate precolonial African history, when written documents produced by Africans were, in some societies, rare or totally absent.